Independence of seasonal patterns of root functional traits and rooting strategy of a grass‐clover sward from sward age and slurry application. (13th April 2016) - Chen, S.‐M.; Lin, S.; Loges, R.; Reinsch, T.; Hasler, M.; Taube, F.
Abstract: Root functional traits (RFTs) are crucial for understanding nutrient cycling processes. However, seasonal variation of RFTs and their potential changes in root foraging pattern have been almost ignored in field studies. In this work, belowground net primary production (BNPP, g m −2 ), root length density (RLD, km m −2 ), specific root length (SRL, m g −1 ), root N concentration and C/N ratio in defoliated grass‐clover swards of different sward ages and receiving different cattle slurry levels were investigated for 2 years. All measured RFTs showed significant seasonal variation: in general, seasonal variation was most marked between primary growth period (until heading stage of perennial ryegrass) and subsequent regrowth periods following defoliation; meanwhile, the rooting pattern also differed. These phenomena were not affected by current management or sward composition, but were correlated with plant C availability. Daily BNPP and RLD rates varied 7‐ to 8‐fold in the growing season. Moreover, BNPP and RLD were asynchronous due to seasonal variation in SRL. Rooting pattern and the relationship with shoot phenology are discussed. We conclude that root functional traits vary with season; thus, roots which develop in different seasons may be involved in belowground nutrient cycling processes with different turnover characteristics; trade‐off among traits may also involve temporal variation. Root‐C related investigations in grass‐clover swards should include root mass sampling rather than use of root length observations alone.